2022
DOI: 10.1111/jace.18456
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance regulation of high‐entropy rare‐earth disilicate for thermal environmental barrier coating materials

Abstract: We prepared the novel high‐entropy (xRE1/x)2Si2O7 (RE = Y, Yb, Er, Sc, Gd and Eu, x = 2–6) ceramics by a two‐step method for the application of thermal environmental barrier coatings (TEBCs), and the effect of configuration entropy and lattice distortion on microstructures and thermal properties at high temperature were investigated. The results showed that the configuration entropy resulted from mass disorder can only contribute to the stability of thermal properties and microstructure. Lattice distortion sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…[Tb] along with CTE data extracted from the literature from dilatometry and high-temperature XRD techniques for RE 2 Si 2 O 7 [54,60,65,66], listed in Tables II and III, and plotted against the average RE cation radius in Figure 3.…”
Section: Thermal Expansionmentioning
confidence: 99%
“…[Tb] along with CTE data extracted from the literature from dilatometry and high-temperature XRD techniques for RE 2 Si 2 O 7 [54,60,65,66], listed in Tables II and III, and plotted against the average RE cation radius in Figure 3.…”
Section: Thermal Expansionmentioning
confidence: 99%
“…High‐entropy RE silicates, referring to a multiprincipal solid solution consisting of four or more RE components, have attracted wide attention due to its outstanding molten CMAS corrosion resistance and lower thermal conductivity 15,16 . Wang et al 17 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 High-entropy RE silicates, referring to a multiprincipal solid solution consisting of four or more RE components, have attracted wide attention due to its outstanding molten CMAS corrosion resistance and lower thermal conductivity. 15,16 Wang et al 17 prepared a high-entropy RE disilicate (5RE 0.2 ) 2 Si 2 O 7 (RE = Yb, Y, Lu, Sc, and Gd) and found that the high-entropy RE disilicate exhibited a good molten CMAS corrosion resistance, and the thickness of the apatite reaction layer was only 25 μm after corrosion at 1400 • C for 20 h. Wang et al 13 also reported the molten CMAS corrosion resistance of a high-entropy (4RE 0.25 ) 2 Si 2 O 7 (RE = Er, Tm, Yb, and Lu) at high temperature. The results showed that the thickness of reaction layer was approximately 300 μm after corrosion at 1500 • C for 50 h. Tian et al 18 only measured the ability of highentropy RE monosilicate ((xRE 1/x ) 2 SiO 5 (RE = Ho, Lu, Yb, and Eu)) to resist molten CMAS corrosion at low temperature, and its thickness of reaction layer was up to 125 μm after corrosion at 1300 • C for 20 h. Therefore, we conclude that although the high-entropy RE silicates showed a significant improvement in the corrosion resistance of molten CMAS compared to single-component RE silicates, the thickness of the reaction layer was still very high during long-term corrosion at high temperature, which will be catastrophic for EBCs with the thickness of only tens to hundreds of microns.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high‐entropy rare‐earth zirconates and silicates had been extensively investigated 23–25 . Ren et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high-entropy rare-earth zirconates and silicates had been extensively investigated. [23][24][25] Ren et al found that the (Y 1/4 Ho 1/4 Er 1/4 Yb 1/4 ) 2 SiO 5 bulk material displayed improved properties, such as Young's modulus, thermal conductivity, and thermal expansion, indicating that it might be a T/EBC candidate. 23 Liao et al prepared (Y 1/3 Dy 1/3 Er 1/3 ) 2 SiO 5 , (Y 1/3 Dy 1/3 Lu 1/3 ) 2 SiO 5 , (Y 1/4 Dy 1/4 Ho 1/4 Er 1/4 ) 2 SiO 5 , and (Yb 1/4 Dy 1/4 Ho 1/4 Er 1/4 ) 2 SiO 5 bulk materials, which possessed lower CTE and thermal conductivity than that of the single-component RE 2 SiO 5 .…”
mentioning
confidence: 99%